OPTIMASI HPMC DAN XANTHAN GUM SEBAGAI MATRIKS TABLET LEPAS LAMBAT KAPTOPRIL MENGGUNAKAN METODE Simplex Lattice Design (SLD) - Sari, Sandra Eka Purna; Aisyah, Siti; Harjanti, Reslely (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Captopril extended-release preparations are preparations that are modified to maintain the drug at therapeutic blood or tissue levels thereby reducing fluctuations in plasma concentrations. The aim of this research was to determine the effect of a combination of HPMC and xanthan gum matrices on the physical properties of captopril extended-release tablets, as well as to determine the best concentration of HPMC and xanthan gum to obtain captopril sustained-release preparations with optimum physical properties. The preparation of the preparation used the wet granulation method and used 8 runs of the Design Expert Simplex Lattice Design with a concentration ratio of HPMC and xanthan gum. Research results have shown that the higher concentration of xanthan gum can increase tablet hardness, reduce tablet friability, and can inhibit the initial release of active substances so that the drug release rate becomes slower. The optimum formula for extended-release captopril tablets resulting from optimization was HPMC 8060-N 25.496 mg, xanthan gum 49.504 mg with a hardness of 15.668 kg, a friability of 0.026 g/second, and a dissolution rate of 45.512%. The release profiles of captopril extended release tablets in this study all followed the Higuchi model release kinetics except for formulas 4, 6, formula 8 which followed zero order release kinetics.